Advances in controlled-release fertilizers - Shaviv, Avi (Advances in Agronomy, 2001)
The steady increase in population growth and food demand and the continuous reduction in cultivated land per capita induce steady intensification of fertilizer application worldwide. Despite improvements in the practices of nutrient application, the use efficiency (UE) of essential elements such as N and P is not satisfactory, resulting in an increase of environmental problems. The use of controlled-release fertilizers (CRFs) starts to evolve as a promising direction offering an excellent means to improve management of nutrient application and by this reducing significantly environmental threats while maintaining high crop yields of good quality. Low cost effectiveness and limited recognition of the potential benefits to be gained from the CRFs were so far the main reasons for their limited consumption. A systematic classification of the slow- and controlled-release fertilizers (SRF/CRFs) and details about the production and action mechanisms of the more common products is given in this chapter. The difference between slow and controlled release is emphasized, stressing the importance of proper synchronization of nutrient supply with plant demand as crucial for achieving the expected benefits from SRF/CRFs. Fertilizers based on polymer coating are singled out as the CRFs offering the best control over release. These are also the ones with the largest growth rate among the SRF/CRFs. Special attention is devoted to the description of release mechanisms and recent developments in modeling release which are essential for predicting nutrient release under real conditions and which can provide the technologists with tools for better design of CRFs. The use of SRF/CRFs in agriculture and nonfarm applications is described, stressing the need to better assess the agronomic and the environmental benefits to be gained. This, together with technological improvements in production of CRFs, is believed to significantly promote the future use of SRF/CRFs in practice. Finally, the efforts to improve the characterization of CRFs are described and a scheme for a systematic evaluation and classification of CRFs is offered. These efforts are likely to promote standardization of the different SR/CR products. By proper labeling, they will also assist legislators and producers in educating consumers about the relevant features of CRFs (e.g., release pattern and duration, and content of available forms).